Log on and blog: An exploratory study assessing the impact of holiday blogging on student literacy achievement. Issue 2 (4th September 2017) - Williamson, Rachel; Jesson, Rebecca
Abstract : Purpose: This paper aims to investigate the viability of blogging over the summer holidays as an intervention to ameliorate the Summer Learning Effect (SLE) in writing. The SLE is the impact on achievement of taking a break from school over summer, and has been documented to affect differentially those students who come from low socioeconomic status (SES) communities compared with their more affluent peers. However, previous studies within similar communities suggest that the effect is not inevitable, and is amenable to intervention. Design/methodology/approach: The present study is set in a group of low SES schools where students already have individual learning blogs. The Summer Learning Journey was designed by the research team in consultation with students and teachers from the schools and trialled in January 2015. The design of the programme drew on previous research that suggested that students would be motivated by interest, rather than achievement, and that literacy activity over summer should be leisure-based. Findings: Initial evidence suggests that students who participated made measurable improvements compared with their own progress over the previous summer and also compared with a matched control group of students, and that the observed difference continued over the 2016 school year. Research limitations/implications: The study provides initial evidence of quite substantial differences in achievement for those students who were active bloggers. Originality/value: The study provides an alternative direction from current summer learning programmes and indicates the potential for designing digital opportunities for learning at times when the school is not in session.